The association between protein intake and feeding practice with stunting in children aged 24-59 months. - Sari, Atri Novembela; Diana, Fivi Melva; Nur, Nadia Chalida (Nutrición Clínica y Dietética Hospitalaria, 2025)
Introduction Stunting is a condition characterized by impaired growth due to prolonged malnutrition, especially during the critical first 1,000 days of life. This condition is identified by comparing a child's height to their age. This research aims to evaluate respondent characteristics and examine the relationship between family income, feeding practices, protein intake, and stunting among toddlers aged 24-59 months. Method This study utilized a cross-sectional design and included 171 toddlers aged 24-59 months residing in the Koto Mudik IV Health Center area, Pesisir Selatan Regency. The sample was selected using proportional random sampling. Family expenditure data were collected through the Home Observation for Measurement of Environment (HOME) questionnaire, while feeding practices were assessed with the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Protein intake was determined by calculating the average daily protein consumption of toddlers and comparing it with the recommended dietary allowance. Statistical analysis was conducted using the chi-square test. Result The findings revealed that 34.5% of toddlers experienced stunting, 59.1% came from families with incomes below the Provincial Minimum Wage (UMP), 56.1% had inadequate feeding practices, and 31.6% experienced a protein intake deficit. Moreover, 56.1% of fathers and 53.2% of mothers had senior secondary school education, while 66.7% of fathers worked as farmers and 79.5% of mothers were homemakers. Significant correlations were observed between family income (p-value=0.017), feeding practices (p-value=0.007), protein intake (p-value=0.002), and stunting in toddlers aged 24-59 months. Conclusion Family income, parental feeding practices, and protein intake play a significant role in the occurrence of stunting among toddlers aged 24-59 months. Increasing animal protein consumption may serve as an effective strategy to combat stunting.